Overview of the Absurdity of Sekartaji Characteristics in the Phenomenon of Pacitan City Traditional Art - Ajisanta, Robet; Djatiprambudi, Djuli; Trisakti, Trisakti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The Sekartaji character is one of the characters in the Panji puppet story. It seems that the Panji and Sekartaji stories themselves have many oral and written versions. In addition, the characterization of Sekartaji has undergone many cycles in each version of the story. Meanwhile, in each cycle of its era, the character of Sekartaji has undergone many developments in the transformation of the story which has been adapted in the form of phenomena of traditional arts. This research observes every phenomenon of traditional arts in the city of Pacitan, where each characterization of Sekartaji is very popular as a symbolization in several traditional art events. This phenomenon creates an absurdist perspective and makes Sekartaji's characterization on the side of liminality. From this analysis, this study will explore the absurdity of Sekartaji's characterization of the traditional Islamic phenomenon in the city of Pacitan using the ethnographic method.